Electrical Palestine : Capital and Technology from Empire to Nation - Meiton, Fredrik (Book collections on Project MUSE., 2019)
"Like electricity, political power travels through physical materials whose properties govern its flow. Electrical Palestine charts the construction of Palestine's electric grid in the interwar period and its implication in the area's rapid and uneven development. It does so in an effort to rethink both the origins of the Arab-Israeli Conflict and the interplay of politics, capital, and technology more broadly. The study follows the co-evolution of the power system and Zionist state-building efforts in Palestine on the conceptual and material level. Conceptually, the design and construction of the system shaped Palestine as a precisely bounded entity with a distinct political, social, and economic character. Materially, the borders of the mandate were mapped onto the power system and structured an ethno-national division of capital, land, and labor. In 1948, these co-evolving forces ultimately carried over into Jewish statehood and Palestinian statelessness"--Provided by publisher.